Patient and Doctor Delays in Smear-Negative and Smear-Positive Pulmonary Tuberculosis Patients Attending a Referral Hospital in Istanbul, Turkey - Gulbanu Horzum Ekinci; Esra Karakaya; Esra Akkutuk Ongel; Osman Haciomeroglu; Adnan Yilmaz (The Scientific World Journal)
Objectives. To measure delays from onset of symptoms to initiation of treatment in patients with smear-negative and smear-positive pulmonary tuberculosis and to identify reasons for these delays. Methods. A total of 136 newly diagnosed pulmonary tuberculosis patients were interviewed using a structured questionnaire. Results. The patients were divided into two groups. Group 1 included 65 smear-negative patients. There were 71 smear-positive patients in group 2. The median application interval was 10 days in group 1 and 14 days in group 2. While 24.6% of the patients had patient delay in group 1, patient delay was present in 33.8% of the patients in group 2 (P>0.05). The median health care system interval was 41 days in group 1 and 16 days in group 2 (P<0.0001). The most common reason for patient delay was neglect of symptoms by patient in both groups. A low index of suspicion for tuberculosis by physicians was the most common reason for doctor delays. Conclusions. Delays are common problem in smear-negative and smear-positive pulmonary tuberculosis patients. Delays should be reduced to reach an effective tuberculosis control. Education of public and physicians about tuberculosis is the most important effort to reduce delays.